Hotel Artemis - Pearce, Drew, 1975-; Foster, Jodie; Brown, Sterling K.; Goldblum, Jeff, 1952- (Universal City, CA : Global Road/Universal Pictures Home Entertainment, 2018)
In the midst of a riot-torn Los Angeles, a mysterious woman named the Nurse runs a secret emergency room and hospital for criminals.
Originally released as a motion picture in 2018.
Wide screen 1.85:1.
Features: audio commentary.
Jodie Foster, Sterling K. Brown, Jeff Goldblum, Sofia Boutella, Brian Tyree Henry.
MPAA rating: R.
Keywords: Criminals -- Drama; Medical drama; Nurses -- Drama; Crime films; Action and adventure films; Fiction films; Thriller films; Feature films